Fabrication of measuring tool for gear rotational speed using an inductive proximity sensor and an Arduino Uno microcontroller - Elfi Susilawati; Yulkifli Yulkifli; Zulhendri Kamus (PILLAR OF PHYSICS, 2017)
The development of science and technology (Science and Technology) always improved. Science and technology proven to provide convenience and benefits for humans as in the field of Physics, for example measurement of the Rotational speed. Rotational speed can be measured in two ways: manually and automatically. Automatic sensor-assisted system used to detect and monitor the speed of play. Sensors for this system is inductive proximity sensors npn LJ12A3-4-Z / BX type. The use of these sensors has not been widely used in general, so the design and realization of the system is done looking at technical data, specifications and sensor characteristics. The objective of the research is to know the performance specification and the design of the gear speed measuring instrument. This research is engineering research. Data collection is done directly and indirectly. Direct measurements are made by comparing the measurements and theoretical outcomes. Indirect measurements determine the precision and accuracy of the speed. The data obtained through measurement are statistically and graphically. Based on data analysis put forward two important sections. First, the measurement system performance specification using proximity sensor and arduino microcontroller UNO consist of DC motor there are 12 gear, near DC motor there is proximity sensor with 4 mm distance to gear, and box circuit. Design specifications of measuring instruments in the form of device sensitivity 8,015; Relative accuracy 0.97; 97% accuracy and 0.99 system accuracy